Evaluating the antiemetic administration consistency to prevent chemotherapy-induced nausea and vomiting with the standard guidelines: a prospective observational study - Vazin A; Eslami D; Sahebi E (Dove Medical Press, 2017)
Afsaneh Vazin, Davood Eslami, Ebrahim Sahebi Department of Clinical Pharmacy, Faculty of Pharmacy, Shiraz University of Medical Sciences, Shiraz, Iran Abstract: Nausea and vomiting (NV) are the most prevalent adverse effects of chemotherapy (CT). This study was conducted to evaluate adherence of the health care team to standard guidelines for antiemetics usage to prevent acute chemotherapy-induced nausea and vomiting (CINV) in a large CT center. A prospective study was performed during an 11-month period on patients receiving CT. A form was designed to collect patients’ demographic information and their chemotherapeutic and antiemetic regimen data. The Likert scale was used to measure the effectiveness of the antiemetics in patients. In this study, the effect of patient-related risk factors on the incidence rate of CINV was examined. Based on the results, CINV events were reported by 74.4% of patients. The antiemetic regimen of 71.2% of the patients complied with the guidelines. The complete response, complete protection, and complete control end points did not differ significantly between patients undergoing guidelines-consistent prophylaxis or guidelines-inconsistent prophylaxis. The females clearly showed a higher incidence rate of CINV (P=0.001) during the first course of CT (P=0.006). A history of motion sickness did not affect the incidence of NV. The maximum compliance error occurred for the use of aprepitant, as 16.16% of the patients who were receiving aprepitant did not comply with its instructions. The results of this study highlight how CINV was controlled in this center, which was significantly lower than that of the global standard. Perhaps, factors such as noncompliance to antiemetic regimens with standard guidelines and the failure to adhere to the administration instructions of the antiemetics were involved in the incomplete control of CINV. Keywords: antiemetics, nausea, vomiting, chemotherapy